2014
DOI: 10.1042/bj20130894
|View full text |Cite
|
Sign up to set email alerts
|

The NTP pyrophosphatase DCTPP1 contributes to the homoeostasis and cleansing of the dNTP pool in human cells

Abstract: The size and composition of dNTP (deoxyribonucleoside triphosphate) pools influence the accuracy of DNA synthesis and consequently the genetic stability of nuclear and mitochondrial genomes. In order to keep the dNTP pool in balance, the synthesis and degradation of DNA precursors must be precisely regulated. One such mechanism involves catabolic activities that convert deoxynucleoside triphosphates into their monophosphate form. Human cells possess an all-α NTP (nucleoside triphosphate) pyrophosphatase named … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 33 publications
0
68
0
Order By: Relevance
“…We have previously shown that media supplementation with an excess of deoxycytidine induces an increase in the expression of DCTPP1 in HeLa cells (12). Hence, we expected that exposure to decitabine might induce a similar modulation of enzyme levels in response to the accumulation of aza-dCTP.…”
Section: Dctpp1 and Dutpase Expression Is Up-regulated In Response Tomentioning
confidence: 92%
See 4 more Smart Citations
“…We have previously shown that media supplementation with an excess of deoxycytidine induces an increase in the expression of DCTPP1 in HeLa cells (12). Hence, we expected that exposure to decitabine might induce a similar modulation of enzyme levels in response to the accumulation of aza-dCTP.…”
Section: Dctpp1 and Dutpase Expression Is Up-regulated In Response Tomentioning
confidence: 92%
“…Cell lines were cultured in a humidified atmosphere of 5 % CO 2 at 37 ºC. quantified and subjected to hydrolysis with formic acid as previously described (12).…”
Section: Cell Cultures and Transfectionsmentioning
confidence: 99%
See 3 more Smart Citations